Calidad del agua del estero Maconta afectada por descargas de la planta de tratamiento de aguas residuales del cantón Tosagua - Coronel Macías, Joselyn Emilia (2022)
The objective of this research was to evaluate the impact on the water quality of the Maconta estuary due to the discharge of wastewater from the Wastewater Treatment Plant of the Tosagua canton. We proceeded to diagnose the status of the WWTP discharges, by collecting prior information and interviews with the technicians in charge of the plant, obtaining that their water discharges are under the current environmental law. Subsequently, the ICA - NSF, ICA Torres, and ICA Olguín et al. water quality indices were applied at 5 sampling points with 3 individual samples in March, May and July and fecal coliform parameters, pH, nitrates were analyzed in the laboratory., total phosphorus, phosphates, BOD5, temperature, turbidity, total solids, suspended solids and dissolved oxygen. The water of the estuary has a medium to poor quality according to the ICA-NSF; a poor quality according to the ICA Torres; and moderately contaminated to contaminated based on the ICA of Olguín et al. Finally, the results of the analyzed parameters were compared with the maximum permissible limits established by Ministerial Agreement 097A, concluding that most of the parameters are within the permissible limits for use in agricultural and livestock activities, except for fecal coliforms. and mainly dissolved oxygen. An analysis of variance of one factor was also applied, which showed that there are no significant differences between the means of the ICA of each of the samples.